Desempenho acústico em sistemas construtivos de pisos de edificações com a utilização de materiais alternativos de construção - Henneberg, Fernanda Aparecida (2022)
In the civil construction sector, the need for technological projects with sustainable characteristics is remarkable, and that seek better criteria of technical quality and comfort in a building. Still, in this context, there is a growing concern in constructive solutions that also positively interfere in the acoustic performance of a building. In view of this perspective, the main objective of this research is to design special systems for building screeds using alternative construction materials, and to evaluate the acoustic performance to impact noise in construction systems, through criteria indicated by specific standards. Regulations, rigorously determining the impactweighted sound pressure level in special flooring systems of autonomous units. For this, compositions were characterized for the manufacture of special flooring systems based on construction and demolition waste (RCD) with technical criteria of quality and performance, in accordance with what advocates good engineering technique. The methodological approach consisted of an exploratory research, from the search for solutions through applied research, using the method of experimental technical procedure. With the results found, it is concluded that all flooring systems with the alternative materials used in this research presented acoustic performance compatible with conventional executive solutions. The presence of the floor coverings attenuated the impact noise level on all the slabs. The inclusion of expanded clay in the mixtures presented superior acoustic performance in relation to the other compositions. Among the flooring systems created and analyzed in this research, three of them stand out, being the special subfloor RCC1, containing RCD sand in the proportion of 70% and 30% of natural sand, with laminate flooring with the result of 45 dB ; the special subfloor RCC3 containing RCD sand in the proportion of 70% and 30% of natural sand and addition of expanded clay, with laminate flooring with the result of 44 dB reached; and the special subfloor RCC3 containing RCD sand in the proportion of 70% and 30% of natural sand and addition of expanded clay, with granite flooring with the result of 44 dB reached; being classified with superior acoustic performance (≤ 45 dB) according to NBR 15575 (2021), having a reduction in the weighted impact sound level on floor systems (Δlw) of 31 dB, 32dB and 31dB, respectively, in relation to slab zero of the acoustic chamber used as a reference value. Finally, it is noteworthy that, in addition to sound attenuation, the special flooring systems built present a great environmental benefit, by recycling construction and demolition by-products (RCD), and other recycled materials such as the use of rubber scraps. , arising from the tire recapping process.